Cloning And Expression Of Nucleocapsid Protein Of Newcastle Disease Virus Fused With Vp5 Gene Of Infectious Bursal Disease Virus - Zaid, Shaherny (2007)
Infectious Bursal Disease Virus (IBDV) is a constant threat to the poultry industry worldwide. This virus encodes a non-structural protein VP5 (17 kDa) that is capable of inducing apoptosis and may play an important role in pathogenesis of IBD. The nucleoprotein (NP) of Newcastle Disease Virus (NDV) has been shown possible to be use as a general carrier. In this study, the C-terminal end of NP full-length (pTrcHis2) were fused to the full-length of VP5 of IBDV to study the effect of these construct in cell culture and the possibility of this recombinant to induce apoptosis. The clones were then expressed and solubility test were done to determine the level of solubility of the recombinant proteins by Western blot. The DNA insert of NPfl-VP5 and VP5 were further subcloned into pCDNA3.1/V5 TOPO TA vector. The pcDNA3.1-NPfl-VP5 and pcDNA3.1-VP5 constructs were tested for transient expression in Chinese hamster ovary (CHO) cells. DNA laddering analysis and Acridine orange propidium iodide (AOPI) was also performed in order to check for any changes due to apoptosis. Expression of the NPfl-VP5 protein in E. coli was not detected by SDS-PAGE but a band at the expected size (~ 70-80 kDa) was detected using Western. Only 5% of this protein was soluble. The PCR products of NPfl-VP5 (1.9 kb) and VP5 (447 bp) were subcloned into pcDNA3.1 vector. The CHO cells that were used in in vitro expression were successfully transfected with the plasmid contain the inserts. After 48 hours post-transfection, the cells that were transfected with pcDNA3.1-NPfl-VP5 and pcDNA3.1-VP5 plasmids exhibited apoptosis. In contrast, no apoptosis was observed in the cells transfected with pcDNA3.1 vector only. To confirm that apoptosis had occurred, at 48 hours post-transfection, the cellular DNA was extracted and analyzed by 2% agarose gel electrophoresis. A laddering effect indicative of nucleosomal fragmentation, was detected in the DNA samples obtained from the cells transfected with pcDNA3.1-NPflVP5 or with pcDNA3.1-VP5 but not with the samples from cells transfected with pcDNA3.1 vector only. The expression of NPfl-VP5 and VP5 proteins in transfected CHO cells were detected by Western blot analysis using anti-V5, anti-NDV, anti-IBDV and anti-VP5 antibodies. Further investigation using AOPI methods also confirm the apoptosis effects. Statistical analysis showed that the percentage of apoptosis cells was significantly higher when transfected with pcDNA3.1-NPflVP5 compare with pcDNA3.1-VP5. As a conclusion, the recombinant protein was successfully constructed and NP can be used as a carrier, and the fusion of NP to VP5 will induce more apoptosis. However, it just slightly increases its solubility. Thus, the results showed that recombinant protein NPfl-VP5 and also VP5 alone were able to induce apoptosis in cell culture.